1960
DOI: 10.1063/1.1735741
|View full text |Cite
|
Sign up to set email alerts
|

Single-Crystal Magnetic Anisotropy and Magnetostriction Studies in Iron-Base Alloys

Abstract: Single crystals of a number of binary iron-base alloys were grown, fabricated, and tested for magnetic anisotropy (K1) and magnetostriction (λ100 and λ111). The additions made to iron included vanadium, molybdenum, germanium, chromium, titanium, and tin. The anisotropy of iron was lowered by the addition elements with the possible exception of tin. On the other hand, λ100 of iron was generally raised by these addition elements. Only titanium and tin lowered λ100; however, titanium had limited solublilty in iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
7

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(27 citation statements)
references
References 6 publications
2
18
0
7
Order By: Relevance
“…=4.4 × 10 4 J/m 3 ) is close to the reported value of K 1 = 4.2 × 10 4 J/m 3 for bulk Fe 70 Co30 [31], whereas for d = 14.3 nm, K eff (= 1.7 × 10 5 J/m 3 ) is much larger than that for bulk Fe 70 Co 30 . Such a large effective anisotropy can beFig.…”
supporting
confidence: 86%
“…=4.4 × 10 4 J/m 3 ) is close to the reported value of K 1 = 4.2 × 10 4 J/m 3 for bulk Fe 70 Co30 [31], whereas for d = 14.3 nm, K eff (= 1.7 × 10 5 J/m 3 ) is much larger than that for bulk Fe 70 Co 30 . Such a large effective anisotropy can beFig.…”
supporting
confidence: 86%
“…5) and V (Ref. 6) is consistent with this view. More recently, in 2000, significantly greater values of k c,2 , up to near 340 Â 10 À 6 (:340 microstrain, referred to as lS in this paper), were reported in Fe alloys containing Ga. 7 Large magnetostriction values for these alloys were not observed in the rhombohedral constant, k e,2 .…”
Section: Introductionsupporting
confidence: 66%
“…Hall has shown that λ 100 of bcc Fe increases moderately with the addition of 2%-4% Mo. 13) Figure 12 …”
Section: Magnetostriction Of Fe-ga-ni and Fe-ga-mo Alloysmentioning
confidence: 99%